2012 National Turfgrass Evaluation Program Tall Fescue Test: 2012–2017 Summary Report - Linda R. Parsons; Michael J. Shelton; Megan M. Kennelly; Jason J. Griffin; Jared A. Hoyle (Kansas Agricultural Experiment Station Research Reports, 2018)
Research efforts to improve cultivar quality include selecting for disease resistance and stress tolerance as well as finer leaf texture, a rich green color, and better sward density. Several cultivars included in the 2012 National Turfgrass Evaluation Program Tall Fescue Test performed well and showed good brown patch resistance in south central Kansas throughout the course of the study.
Keywords: brown patch; resistance; tall fescue; transition zone; National Turfgrass Evaluation Program; NTEP